Analisis Pilihan Konsumen Terhadap Barang Substitusi dan Komplementer - Murbanto Sinaga; Rika Surianto Zalukhu; Rapat Piter Sony Hutauruk; Daniel Collyn; Suci Etri Jayanti. S; Sri Winda Hardiyanti Damanik; Yomeini Margareth (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This study aims to analyze consumer behavior in choosing substitute and complementary goods. The research was conducted on consumers in traditional markets, namely Petisah Market and Simpang Limun Market, as well as modern markets, namely Sun Plaza and Plaza Medan Fair in Medan City. The research sample consisted of 200 respondents selected using a purposive sampling method. The primary research instrument was a structured questionnaire designed with a five-point Likert scale to measure respondents' perceptions of factors influencing their choices, such as the price of goods. The data were analyzed using both quantitative and qualitative approaches. Quantitative analysis involved descriptive statistics to describe the characteristics of respondents and data distribution. The analysis results indicate that consumers tend to choose substitute goods when the price of primary goods increases. Furthermore, price significantly influences purchasing decisions for both substitute and complementary goods. Consumers are more sensitive to price changes in substitute goods due to their tendency to seek cheaper alternatives. In contrast, for complementary goods, an increase in the price of primary goods tends to reduce the demand for complementary goods, as they are often used together. The implications of this study suggest that appropriate pricing strategies can optimize the demand for substitute goods, while careful consideration is needed when setting prices for complementary goods.